TERMINOLOGI TA’DIB DALAM PERSPEKTIF SYED MOHAMMAD NAQUIB AL-ATTAS - Abdul Rosyad; Wasehudin (Journal of Innovation Research and Knowledge, 2022)
This paper tries to discuss the concept offered by Al-Attas. His thinking is seen as fundamental because the concept is different from the terms that are already popular in the world of Islamic education. According to Al-Attas, the right concept for Islamic education is Ta'dib, not Tarbiyah or Ta'lim. Because ta'dib already includes the meaning of tarbiyah and ta'lim. Tarbiyah termsAs a concept of education, according to him, it is not appropriate to show education in the meaning of Islam, because education in Islam is intended only for humans while tarbiyah includes humans and others. While the word ta'lim has a special connotation and refers to "science", so the concept of ta'lim has the meaning of "teaching knowledge", or making someone knowledgeable. In contrast to Ta'dib which has the same root as the word adab, according to al-Attas, he emphasizes that the knowledge gained can be practiced well and not misused according to the free will of the knowledge owner, because knowledge is not value free but value laden.), namely Islamic values ​​that require the perpetrators to practice them for the benefit and benefit of mankind. Education is an effort to create a good (universal) human being in accordance with the main function of its creation, and education is a means of transforming noble moral values ​​originating from religious teachings into humans, as well as being the basis for the process of Islamization of science in order to stem the influence of the West. which tends to materialism, secularism, and the dichotomy of science